2021
DOI: 10.3233/rnn-201073
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Oleocanthal protects against neuronal inflammation and cardiopulmonary bypass surgery-induced brain injury in rats by regulating the NLRP3 pathway

Abstract: Background: Open heart surgery is performed with the aid of cardiopulmonary bypass (CPB) techniques that may cause neuronal injuries. Objective: This study investigated the potential protective effect of oleocanthal pre-treatment against CPB-induced cerebral injury. Methods: Oleocanthal 30 mg/kg i.p. was administered 3 h before CPB induction in the treated group. Behavioral neurological scores and cerebral injury were assessed to determine the effects of oleocanthal, based on oxidative stress and serum mediato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Several research groups reported the anti-oxidant and anti-inflammatory activities of oleocanthal and oleuropein [30][31][32][33][34][35][36][37], while those of OLC are still poorly defined. Recently, it has been shown that OLC exerts anti-inflammatory effects in human adipocytes challenged with TNF-α, a prototypic inflammatory stimulus, which could aid to explain the cardiometabolic benefit of EVOO consumption [32].…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups reported the anti-oxidant and anti-inflammatory activities of oleocanthal and oleuropein [30][31][32][33][34][35][36][37], while those of OLC are still poorly defined. Recently, it has been shown that OLC exerts anti-inflammatory effects in human adipocytes challenged with TNF-α, a prototypic inflammatory stimulus, which could aid to explain the cardiometabolic benefit of EVOO consumption [32].…”
Section: Introductionmentioning
confidence: 99%
“…These regulatory mechanisms of vasoconstriction are deregulated, to a greater or lesser extent, during and after the cardiopulmonary bypass ends (Figure 3). The passage of blood through CPB stimulates the activation of the complement cascade, production of ROS species and release of inflammatory mediators, such as the triad of cytokines, interleukin-1 (IL-1), interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) [45,[75][76][77][78]. All this inflammatory biochemistry is capable of acting in specific areas of the brain such as the locus coeruleus and the paraventricular nucleus of the hypothalamus, where the cells responsible for the hypothalamic-pituitary-adrenal axis are located; they stimulate these regions and lead to a reduction and desensitization of the alpha-1 adrenergic receptor and an increase in the inflammatory state, thus forming a cycle that is difficult to overcome (11).…”
Section: Vasoplegiamentioning
confidence: 99%